LANDASAN TEOLOGIS MANAJEMEN PENDIDIKAN ISLAM: Theological foundations and their implications in Islamic education management: a conceptual perspective - Hariyanto, Teguh; Tamlekha, Tamlekha; Ihsanda, Nu'man; Hambali, Adang; Basri, Hasan (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
Effective Islamic education management necessitates a robust theological foundation to ensure that institutional practices remain aligned with the core principles of Islam. A comprehensive theological understanding not only guides the formulation of educational policies and strategic directions but also shapes the underlying values, ethics, and objectives of Islamic education. Employing a conceptual framework and literature review methodology, this study critically examines Islamic theological sources, scholarly documents, and prior empirical research related to educational management. The analysis highlights that the principles of tauhid (divine unity), akhlaq (ethical conduct), and sharia (Islamic law) constitute the fundamental pillars of management within Islamic educational institutions. These theological tenets influence key managerial functions, including curriculum development, character formation, human resource management, and administrative governance. Integrating these values into management practices not only ensures coherence with Islamic teachings but also enhances educational quality, teacher professionalism, and stakeholder trust. The study underscores the imperative of embedding theological values as a strategic framework for achieving holistic and sustainable Islamic education.